Re-functioning of Gashouses as an Example of Industrial Heritage: Hasanpaşa Gashouse - Ayvaz, Ebru; Halaç, Hicran Hanım (Fırat Üniversitesi, 2023)
Industrial heritage buildings could not meet the needs of the age with the development of technology and lost their functions in the city they were in and became inactive. The fate of industrial buildings, in which all the features of the period they were built are reflected, started to be discussed especially in the second half of the 20th century and the concept of industrial heritage emerged. The concept of re-functioning comes to the fore in preserving the cultural heritage values and architectural identities of these structures and transferring them to future generations. At this point, industrial structures that lost their function in the city are re-functionalized and participate in the city life. In this study, it is aimed to examine the functional change of Hasanpaşa Gashouse, which was re-functionalized and transformed into a public space, and the environmental effects of the change in function. The effects of the converted Hasanpaşa Gashouse on the historical area where it is located and the positive results of the re-functioning interventions have been determined by the survey study applied to the users visiting the area. As a result of the survey, it has been reached that the gashouse has become a part of the city and become an active public space with the re-functioning, adopted by the citizens, and its transformation has been successful with the sustainable preservation of its place in the city's memory.

Endüstriyel miras yapıları teknolojinin gelişmesiyle çağın ihtiyaçlarını karşılayamayarak bulundukları kent içinde işlevlerini yitirip âtıl duruma gelmişlerdir. İnşa edildikleri dönemin tüm özelliklerinin yansımalarının görüldüğü endüstri yapılarının akıbeti, özellikle 20. yüzyılın ikinci yarısı itibariyle tartışılmaya başlanmış ve endüstriyel miras kavramı ortaya çıkmıştır. Bu yapıların sahip olduğu kültürel miras değerlerinin ve mimari kimliklerinin korunarak yaşatılması ve gelecek kuşaklara aktarılmasında yeniden işlevlendirme kavramı ön plana çıkmaktadır. Bu noktada kent içinde işlevini kaybeden endüstri yapıları yeniden işlevlendirilerek kent hayatına katılmaktadırlar. Bu çalışmada, yeniden işlevlendirilerek kamusal bir alana dönüştürülen Hasanpaşa Gazhanesi’nin işlevsel değişimi ve işlev değişiminin çevresel etkileri kapsamında incelenmesi amaçlanmıştır. Dönüştürülen Hasanpaşa Gazhanesi’nin yer aldığı tarihi alana etkileri ve yeniden işlevlendirme müdahaleleriyle ortaya çıkan olumlu sonuçları alanı ziyaret eden kullanıcılara uygulanan anket çalışmasıyla tespit edilmiştir. Yapılan anket sonucunda gazhanenin yeniden işlevlendirilmesiyle kentin bir parçası haline gelerek aktif bir kamusal alan olma amacına ulaşarak kentli tarafından benimsenerek kent hafızasındaki yerinin sürdürülebilir korunmasıyla dönüşümünün başarılı olduğuna ulaşılmıştır.
ENDÜSTRİYEL MİRAS ÖRNEĞİ OLAN GAZHANELERİN YENİDEN İŞLEVLENDİRİLMESİ: HASANPAŞA GAZHANESİ